Pengaruh Keluhan Kesehatan terhadap Indeks Pembangunan Manusia Di Provinsi Jawa Timur - Nur Isnaeni Novitasari; Suharno Suharno; Arintoko Arintoko (Universitas Batanghari Jambi, 2021)
The Investments in human capital are the same with improving the quality of human development. The success of national development can be seen from the health aspect in the form of measurement indicator of the Human Development Index. This research analyzes the effect of health complaints, unemployment, poverty and government expenditure on the Human Development Index in East Java Province 2015-2018. This research method uses multiple linear regression with a panel data approach. The results showed that health complaints, unemployment and poverty have a negative and significant effect on the Human Development Index in East Java Province. Meanwhile, government expenditure has a positive and significant effect on the Human Development Index in East Java Province. These findings imply 1) the necessity to improve health infrastructure and government expenditure especially in the health sector, 2) the necessity to increase employment opportunities for reducing poverty and unemployment.